Forensic Accounting Techniques and Corruption in the Public Sector of South-West, Nigeria - Alao, O; Adegbie, F. F.; Ogundajo, G. O. (Archives of Business Research, 2023)
Corruption is recognized as a significant global challenge which remains unresolved, Nigeria inclusive. It continues to impede progress, economic growth, and social development. Also, Corruption have been the focus of ongoing literature discussion especially Sub-Saharan Africa, centering on the adverse effects of corruption, hindering post-pandemic recovery and efforts to address economic, ecological, and healthcare challenges. From literature, researchers focused on conventional audit as solution variable. This study, thereby, examined the effect of forensic accounting techniques on corruption in the public sector of South-West, Nigeria. The study adopted a survey research design. The population of the study comprised 395 staff working in the Anti-graft agencies and ministry and departmental agencies in South-West, Nigeria. A sample of 254 respondents was determined using the Krejcie and Morgan formula. The result of Cronbach’s alpha was greater than 0.70 and the AVE was greater than 0.5, the adapted questionnaire was deemed reliable and valid to proceed for analysis. The paper used the two methods of statistics (descriptive statistics and inferential statistics) to analyse the data. Forensic accounting techniques had significant effect on corruption ( Adj R2 = 0.07, F (5, 220) = 4.77, p < 0.05). Audit quality and quality of governance significantly controlled the effect of forensic accounting techniques on corruption (Adj R2 = 0.07, F (7, 218) = 3.42; p < 0.05). The study concluded that forensic accounting techniques affected corruption in the public sector of South-West, Nigeria. It was recommended that the anti-graft agencies and Ministry and departmental agencies should integrate forensic accounting techniques into their processes in order to achieve transparency and accountability in the management of public funds. The governments of South-West, Nigeria must ensure to establish forensic accounting unit where trained expert are employed with attractive remuneration to carry out investigation cases of corruption to ensure enough evidence and facts are presented in courts for effective prosecution of such cases.